2019
DOI: 10.1002/joc.6164
|View full text |Cite
|
Sign up to set email alerts
|

Space–time variability of drought over Vietnam

Abstract: Drought may have severe societal, economic, and environmental consequences. However, the space–time characteristics of drought over Vietnam remain poorly understood. In this study, we investigate the spatio‐temporal variability of drought using the Palmer Drought Severity Index (PDSI) over mainland Vietnam for the 1980–2014 period. Through data analysis at 131 stations, we identified the main characteristics, historical trends, and dominant variability of drought across seven climatic sub‐regions in Vietnam. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 48 publications
1
28
1
Order By: Relevance
“…The drought periods described above are in accordance with the study of Le and colleagues [35], who used monthly precipitation and 2 m air temperature observations for the period 1980-2014 obtained from 131 meteorological stations across mainland Vietnam to calculate PDSI. However, these authors [35] found that in the S5 region the dry conditions were more intense than in the other regions of the country, and this is not clearly noticeable in our results.…”
Section: Drought Conditionsmentioning
confidence: 90%
See 4 more Smart Citations
“…The drought periods described above are in accordance with the study of Le and colleagues [35], who used monthly precipitation and 2 m air temperature observations for the period 1980-2014 obtained from 131 meteorological stations across mainland Vietnam to calculate PDSI. However, these authors [35] found that in the S5 region the dry conditions were more intense than in the other regions of the country, and this is not clearly noticeable in our results.…”
Section: Drought Conditionsmentioning
confidence: 90%
“…Some studies have highlighted that droughts have become unusually more frequent and severe worldwide, such as in the Mediterranean region [21][22][23], Europe [24][25][26], West Africa [27,28], and Asia, including Vietnam [20,[29][30][31][32][33][34][35]. Recent conclusions of the Intergovernmental Panel on Climate Change (IPCC) show much evidence that climate change affects many regions in Southeast Asia, one of the most vulnerable regions in the world [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations